The impact of ketamine on pain-related outcomes after thoracotomy: a systematic review with meta-analysis of randomized controlled trials - Zhaksylyk, Aruzhan; Abdildin, Yerkin G.; Sultangazin, Suienish; Zhumakanova, Aigerim; Viderman, Dmitriy (Frontiers in Medicine, 2024)
Objective: This meta-analysis aims to examine how effective ketamine is in the management of acute and preventing chronic post-thoracotomy pain by synthesizing the available research.Method: A systematic literature search was conducted across PubMed, Scopus, and Cochrane Library till May 23. Randomized Controlled Trials (RCT) examining the influence of ketamine on post-thoracotomy pain in adults were included. The intervention group included ketamine plus morphine, while the control group included morphine only. The outcome measures were opioid intake and pain scores at rest and on moving/coughing. Evidence quality was evaluated using the Cochrane Risk of Bias and GRADE assessment.Results: Nine articles were comprising 556 patients were selected for meta-analysis. The intervention group had a significant decrease in pain at rest (Std. Mean Difference (SMD) = -0.60 [-0.83, -0.37]) and on movement/cough (SMD = -0.73 [-1.27, -0.18]) in the first postoperative days. Also, the ketamine group had lower opioid consumption (mg) in comparison with controls (SMD = -2.75 [-4.14, -1.36], p-value = 0.0001). There was no data to assess the long-term effect of ketamine on chronic pain.This meta-analysis shows that ketamine use can lower acute pain levels and morphine use after thoracotomy. In the future, larger RCTs using standardized methods and assessing both short-term and long-term analgesic effects of ketamine are necessary to deepen the understanding of the issue.